Multitarget drug design strategy in Alzheimer’s disease: focus on cholinergic transmission and amyloid-β aggregation - Simioni, Elena; Bartolini, Manuela; Abu, Izuddin Fahmy; Blockley, Alix; Gotti, Cecilia; Bottegoni, Giovanni; Caporaso, Roberta; Bergamini, Christian; Andrisano, Vincenza; Cavalli, Andrea; Mellor, Ian R.; Minarini, Anna (Future Science, 2017)
Background: Alzheimer pathogenesis has been associated with a network of processes working simultaneously and synergistically. Over time, much interest has been focused on cholinergic transmission and its mutual interconnections with other active players of the disease. Besides the cholinesterase mainstay, the multifaceted interplay between nicotinic receptors and amyloid is actually considered to have a central role in neuroprotection. Thus, the multitarget drug-design strategy has emerged as a chance to face the disease network. Results: By exploiting the multitarget approach, the present study provides new molecules able to target the cholinergic pathway, by joining direct nicotinic receptor stimulation to acetylcholinesterase inhibition, and to inhibit Aβ aggregation. Conclusions: These new compounds emerged as a suitable starting point for a further optimization process.